FACTORS AFFECTING THE INTEREST OF INFORMATION SYSTEM UTILIZATION (Case Study: STMIK ABC) - Mulyati Mulyati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Application of information systems has been widely used in various fields including in the field of education. This study aims to examine the factors that influence interest in the use of information systems, performance expectations on the use of information systems at STMIK ABC. The method used by the author in collecting this data is a questionnaire, data processing and analysis is carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS version 3.2.8 application software. The results of this study indicate that the results of hypothesis testing on the Performance Expectations variable have a significant positive effect on the Interest in Information Systems Utilization (H1), thus H1 is accepted, while the Social Factors Variable Hypothesis test has a significant positive effect on the Interest in Information Systems Utilization (H2) in this way the results of the hypothesis variable Condition Facilitating the User has a positive effect on the Interest in Using Information Systems (H3) so that H3 is accepted. The results of this test identify the variable performance expectations, social factors and conditions that facilitate the user to influence the user's interest in the use of information systems so that it can help improve performance in improving the quality of work output and further improve the quality of teaching and learning at STMIK ABC.